DEVELOPMENT OF THE AUTOMOTIVE INDUSTRY IN THE NEW UZBEKISTAN - Akbarov Iqboljon Ahmadjonovich, (Ustozlar uchun, 2025)
Abstract:This article explores the evolution and current progress of the automotive industry in the context of the socio-economic reforms of the New Uzbekistan. The study examines state support mechanisms, joint ventures with foreign partners, modernization efforts, and the introduction of electric vehicles (EVs) into the domestic market. It also highlights the significance of innovation, localization, and export-oriented strategies that contribute to sustainable industrial development in Uzbekistan.